Use of rifabutin in treatment of systemic Mycobacterium paratuberculosis infection in mice. - Chiodini, R J (1993)
BALB/c mice were infected intraperitoneally with Mycobacterium paratuberculosis and, after allowing the infection to progress for 30 days, were treated with rifabutin at 0, 12.5, 25, and 50 mg/kg of body weight. Rifabutin was administered in drinking water under conditions of water deprivation, whereby the entire daily dose was delivered within a 1-h period. Animals were killed at biweekly intervals from time zero of treatment to 180 days. Spleens and livers from each animal were examined by quantitative bacteriologic culture and histopathology. Restricted water availability was found to be a viable alternative to daily gavage for single-dose bolus administration. Infection, as assessed by bacterial counts, was reduced only in animals that received 50 mg of rifabutin per kg. In these animals, bacterial counts in the liver and spleen were reduced from 7.2 x 10(5) +/- 4.1 x 10(4) and 6.5 x 10(5) +/- 4.1 x 10(4) to 3.0 x 10(3) +/- 1.8 x 10(2) and 3.1 x 10(3) +/- 2.2 x 10(2), respectively, over the 6-month treatment period. Rifabutin may be an appropriate chemotherapeutic drug for long-term treatment of M. paratuberculosis infection and should be considered in any multidrug regimen.